Substituting Partial Chemical Fertilizers with Bio-Organic Fertilizers to Reduce Greenhouse Gas Emissions in Water-Saving Irrigated Rice Fields - Zhengdi Han; Huijing Hou; Xianzi Yao; Xiang Qian; Mingyao Zhou (Agronomy, 2024)
Conventional water and fertilizer management practices have led to elevated greenhouse gas emissions from rice fields and decreased the efficiency of water and fertilizer utilization in agricultural land. The implementation of water-saving irrigation and the substitution of chemical fertilizers with organic alternatives can influence CH4 and N2O emissions in rice fields. However, it remains unclear how the simultaneous application of both methods will affect the CH4 and N2O emissions in rice fields. Therefore, two irrigation methods (F: flooded irrigation; C: controlled irrigation) and three fertilization modes (A: full chemical fertilizer; B: bio-organic fertilizer replacing 15% chemical nitrogen fertilizer; C: bio-organic fertilizer replacing 30% chemical nitrogen fertilizer) were set up through field experiments to explore the effect of greenhouse gas emission reduction in rice fields by combining controlled irrigation and bio-organic fertilizers. Substituting some chemical fertilizers with bio-organic fertilizers can lower the peak CH4 and N2O fluxes in rice fields, leading to a decrease in the cumulative CH4 and N2O emissions by 11.9~29.7% and 10.8~57.3%, respectively. The reductions led to a considerable decrease in the global warming potential (GWP) and the greenhouse gas emission intensity (GHGI) by 16.1~48.1% and 16.3~48.1%, respectively. Controlled irrigation significantly reduced CH4 emissions by 55.2~69.4% compared with flooded irrigation in rice fields. However, it also increased N2O emissions by 47.5~207.9%, considerably reducing their GWPs by 11.8~45.5%. Neither bio-organic fertilizer substitution nor controlled irrigation significantly affected rice yield. Replacing 15% of chemical nitrogen fertilizers with bio-organic fertilizers in controlled irrigation rice fields can minimize rice GWP and GHGI. The study’s results are of significant importance for enhancing the regulation of greenhouse gases in farmland and achieving sustainable agriculture through cleaner production.